I don’t chase, I attract: TikTok, new thought, and the algorithms of divination - Chalfant, Eric (Religion, 2025)
This article argues that the popularity of divination on the digital platform TikTok represents the emergence of a significant new wrinkle in metaphysical religion made possible by digital algorithms and algorithmic culture. This article aims to uncover the implicitly religious ways that some users think about digital culture as well as how engagement with algorithms continues to shape people's inhabitations of religious worlds. For example, New Thought's law of attraction – the idea that external events can be dictated by conscious thoughts – resonates with a digital platform in which the content one attracts is determined by an invisible algorithm that seems to read the mind of the user. Thus, I suggest that the language and practices of New Thought can give voice to feelings generated by experiences of using TikTok while interfacing smoothly with networked forms of power.